Frequency of Metabolic Abnormalities in Pakistani Children With Urinary Lithiasis - Muhammad Tanveer Sajid, Muhammad Rafiq Zafar, Qurat Ul Ain Mustafa, Rabia Abbas, Sohail Raziq, Khurram Mansoor (Société Internationale d’Urologie Journal)
ObjectiveTo determine the frequency of various metabolic abnormalities in children with urinary lithiasis. MethodsThis cross-sectional study was conducted at the Armed Forces Institute of Urology, Rawalpindi, from 30 January 2017 to 1 February 2020. A total of 1355 children who were aged 4 to 14 years and who had renal stones were included, while those with urinary tract infections, posterior urethral valve, pelvi-ureteric junction obstruction, reflux disease, and chronic renal failure were excluded. Twenty-four-hour urine samples were analyzed for urinary uric acid, calcium, oxalate, citrate, and magnesium. Demographics and metabolic abnormalities—hypercalciuria, hyperoxaluria, hypocitraturia, hyperuricosuria, and hypomagnesuria—were noted and analyzed. ResultsThe study analysis included 1355 patients. Low urine volume was observed in 465 (34.3%) of the patients. Three hundred nine patients (22.8%) had metabolic abnormalities, the most common being hypocitraturia (184, 59.5%) followed by hypercalciuria (136, 44%) and hypomagnesuria (126, 40.8%). Mean age of presentation, disease duration, recurrent bilateral stones were found significantly different in those having metabolic abnormalities (7.81±2.25 versus 8.76±2.50 P < 0.001, 7.73±1.50 versus 8.43±1.54 P < 0.001, 19.4 versus 2.4% P < 0.001 respectively). No significant difference was found in frequency of abnormal urinary metabolic parameters between boys and girls (P > 0.05) or, upon data stratification, on the basis of disease duration, stone laterality, and recurrence. ConclusionsMetabolic abnormalities were found in 22.8% % of children presenting with urinary lithiasis. The most frequent abnormality observed was hypocitraturia followed by hypercalciuria and hypomagnesuria. Early identification helps manage such patients appropriately, mitigating long-term sequelae.